Local Wisdom-Based Complementary Feeding for Stunting Prevention: A Qualitative Study Using the Health Promotion Model - Atik pramesti wilujeng; Novita Surya Putri; Tria Anisa Firmanti; Badrul Munif; Dina Puspitasari; Akhmad Yanuar Fahmi Pamungkas (Fakultas Ilmu-ilmu Kesehatan, 2026)
Stunting remains a major health concern in low- and middle-income countries, including Indonesia, where complementary feeding practices are strongly influenced by culture, maternal knowledge, and environmental support. Local wisdom offers a culturally relevant approach for improving child nutrition and preventing stunting. This study aims to explore mothers’ experiences in preparing complementary foods using local wisdom and to analyze these practices through the Health Promotion Model. The researchers applied a qualitative phenomenological approach with ten mothers of undernourished children aged 6–24 months in coastal Banyuwangi. Data were collected through in-depth interviews and analyzed using the Colaizzi method, guided by Health Promotion Model constructs. The analysis revealed five themes: cultural beliefs in food choices, maternal knowledge of nutrition, use of local ingredients, external support from health workers, and sustained maternal engagement in complementary feeding. The findings highlight that complementary feeding grounded in local wisdom can potentially support stunting prevention. Thus, strengthening maternal self-efficacy, addressing barriers, and enhancing social support are critical to improving feeding practices.